Transnational Organising and Feminist Politics of Difference and Solidarity: The Mobilisation of Domestic Workers in Hong Kong. Issue 1 (2nd January 2016) - Lim, Adelyn
Abstract: Domestic work represents a significant share of global wage employment, but domestic workers – the majority of whom are women – remain to a large extent excluded from the scope of labour laws and, consequently, from the legal protection enjoyed by other workers. Since they work behind the closed doors of private homes, domestic workers are also shielded from public attention and are often hard to mobilise. In Hong Kong, women's activism involving local and migrant domestic workers illuminates points of connection and distance as they are simultaneously privileged and marginalised along the hierarchies of class, ethnicity and nationality. Building on feminist and social movement scholarship, I illustrate how global frames facilitate our understanding of feminist solidarity among local and migrant domestic workers. I argue that the meanings of solidarity that dominate at any particular moment are not stable and enduring, but rather formed out of negotiation and struggle within and across domestic workers' unions. This framing process involves these women working deliberately to make connections between global processes and local contexts.